Diagnosis and adaptations of the drinking water cooling system for lactating and gestating swine females with a view to improving production rates (Research, Society and Development, 2021)
Managing lactating sows properly when subjected to thermal stress is essential for the pig industry. The high temperature combined with the high humidity, causes the performance of the lactating matrices to be compromised, as the effects of this heat stress, the sows decrease the food intake and consequently decrease the milk production in the litter. In this way, the objective of this work was to adapt the existing drinking water cooling system in operation at the pig farm at Professor Hamilton de Abreu Navarro Experimental Farm, so that it promotes the recirculation of the water used to feed the swine females, in order to maintain the temperature at levels suitable for consumption by animals. The project was created in order to improve in an economical and efficient way. It installed equipment, added new pipes and a time-controlled motor pump to recirculate the water. After implantation, the water in the pipeline remained more homogeneous and at temperatures lower than that of the mains water and the environment. It was concluded that there was an improvement in the system, which will allow future studies on the influence of chilled water on zootechnical indexes.